2015
DOI: 10.1209/0295-5075/110/15001
|View full text |Cite
|
Sign up to set email alerts
|

Confinement of the charged microparticles by alternating electric fields in a gas flow

Abstract: This paper presents the simulation and experimental results of charged microparticles dynamics in electrodynamic traps in a gas flow at atmospheric pressure. For the first time the capture and confinement of charged microparticles in a linear Paul trap has been experimentally confirmed at atmospheric pressure in gas flows. The regions of the microparticle, linear Paul trap and gas flow parameters needed for microparticle confinement have been obtained and experimentally tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Ref. [350] presents theoretical and experimental studies of charged microparticle capture in a linear Paul trap, in gas flow. The regions of microparticle and trap parameters required to achieve particle confinement are investigated under normal SATP conditions.…”
Section: Applications: the Electrodynamic Trap With Corona Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [350] presents theoretical and experimental studies of charged microparticle capture in a linear Paul trap, in gas flow. The regions of microparticle and trap parameters required to achieve particle confinement are investigated under normal SATP conditions.…”
Section: Applications: the Electrodynamic Trap With Corona Dischargementioning
confidence: 99%
“…The numerical simulation performed in [350] considers a microparticle characterized by a density ρ p = 3.99 g/cm 3 . We mention that U ac stands for the trapping voltage, while R 2 and R 1 represent the radii of the grounded cylindrical shell surrounding the trap and trap electrode respectively.…”
Section: Applications: the Electrodynamic Trap With Corona Dischargementioning
confidence: 99%
“… A new method of particle capture and removal from gas flows by electrodynamic traps has been suggested. Trap examples, their modifications, and the physical parameters needed for particle capture have been obtained. …”
Section: Introductionmentioning
confidence: 99%
“…Linear electrodynamic quadrupole traps were used to create and study stable extended Coulomb structures containing thousands of charged dust particles . Studies have shown that linear traps are able to confine charged dust particles in air flows, and they can be used as selective filters for the purification of air from the dust particles . This paper is devoted to the investigation of the confining conditions of dielectric dust particles located on a dielectric surface under a linear electrodynamic trap and the possibility of cleaning dusty dielectric surfaces with the help of a linear electrodynamic trap.…”
Section: Introductionmentioning
confidence: 99%